Rosendo M. Mejica a bio-bibliography - Ledesma, Teresita R. (1980)
This special problem deals with the bio-bibliography of Rosendo M. Mejica, a pioneer printer-publisher in Hiligaynon, a journalist, a public official, a labor leader, and a philanthropist. It describes the man's contributions to the dissemination of Ilongo thought and culture and presents such contributions through a systematic organization of the Mejica Collection. Considered a vital link to the rich Ilongo past, the collection covers the years from 1913-1941. It consists of issues of the Makinaugalingon, the oldest and one of the most enduring vernacular newspapers in Iloilo, imprints of the Makinaugalingon Press, correspondence, clippings, printed matter, biographical features, memorials, memorabilias, greeting cards, scrapbooks, albums, invitations and programs, photographs, and family records.